Design and Preparation of Activated Carbon with High Specific Surface Area and Porosity Through an Organic Activator Coupled with CO2 Activation - Yizhong Li; Xiaoqing Yan; Zhi Cui; Jingkang Yuan; Baorong Xu; Guidong Yang (Advanced Materials Interfaces)
Abstract The advancement of effective techniques for the production of activated carbon has been a prominent focus of research. Herein, this work designs and successfully prepares a nontoxic, environmentally friendly organic activator on the surface of carbon materials through in situ organic fermentation treatment method. The production of activated carbon via this novel organic activator is at a temperature of 850 °C under CO2 atmosphere for an activation time of 90 min, showing a specific surface area (SBET) of 1354 m2 g−1, an adsorption capacity of iodine (QI) of 1195 mg g−1, and a total pore volume (Vtot) of 0.855 cm3 g−1. Compared to the activated carbon prepared at high temperature under pure CO2, these results represent increases of 69.67%, 53.01%, and 93.44% in SBET, QI, and Vtot values, respectively. By means of thermogravimetric (TG) analysis and simultaneous thermal analysis‐Fourier transform infrared spectroscopy‐gas chromatography/mass spectrometry a suggested activation process and mechanism of the novel organic activators is proposed. This organic activator is not only used for semi‐coke (SC) based activated carbon preparation and saturated activated carbon (SAC) regeneration, but also attracts other industrial activated carbon production.